ESTUDIO CLÍNICO Y ELECTROFORÉTICO DE LA LEISHMANIASIS TEGUMENTARIA EN CAVIDAD ORAL EN ZONA ENDÉMICA DEL VALLE DE LA CONVENCIÓN, CUSCO - Romero R., Roberto (2000)
The work was accomplished in Convention Valley in Cuzco, a community home for field workers called Prodein-Union Lumen Dei and in Quillabamba, in the villages of Maranura, the stopping places of Alto Curibiñe, Chaco y Quetene. Thirty leishmaniásicos cases were studied with vegetating lesions on the palate and thirty control cases. In the vegetative lesion cases with pockets deeper than 5 millimeters, forming "mamelons or moluscos carnosos" which, after the end of the specific treatment, sclerotic scars were left on the palate that hindered swallowing and talking 46.7 % or fourteen cases were found to be serious with this condition. In the electrophoretic study with non-hemolized frozen saline agreed with the histopathalogic study that there was a dropped 30% a 40% in the inmunoglobulins IgA, IgG, and IgM, which hninder the formation of glucosaminoglycogens. The purpose of the work, by means of clinical, histopathologic, and electrophoretic studies, is to apply a proper therapeutic method that contains a larger portion of inmunoglobulin type proteins 60 % a 70 % and at the same time a nutrient that will allow formation on glucosaminoglycogens arriving to correct the sclerotic scaring of the palate.